2010
DOI: 10.1007/s00359-010-0588-3
|View full text |Cite
|
Sign up to set email alerts
|

A central pacemaker that underlies the production of seasonal and sexually dimorphic social signals: anatomical and electrophysiological aspects

Abstract: Our long-term goal is to approach the understanding of the anatomical and physiological bases for communication signal diversity in gymnotiform fishes as a model for vertebrate motor pattern generation. Brachyhypopomus gauderio emits, in addition to its electric organ discharge (EOD) at basal rate, a rich repertoire of rate modulations. We examined the structure of the pacemaker nucleus, responsible for the EOD rate, to explore whether its high output signal diversity was correlated to complexity in its neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…As the pattern of emission of the electromotor output in electric fish is itself a social display [as it signals species, sex, season, status, male quality and social context (Silva et al, 2007;Perrone et al, 2009;Gavassa et al, 2012)], which relies on the activity of a well-known and accessible medullary medial nucleus (the PN) (Pouso et al, 2010;Quintana et al, 2011a;Quintana et al, 2011b), electric fish appear as a good model system to target specific brain areas of AVT actions. In a previous study, Perrone et al (Perrone et al, 2010) demonstrated that AVT induced a long-lasting and progressive increase of EOD rate in isolated B. gauderio, but had no effects in G. omarorum.…”
Section: Differential Avt Modulation Of Two Types Of Aggressionmentioning
confidence: 99%
“…As the pattern of emission of the electromotor output in electric fish is itself a social display [as it signals species, sex, season, status, male quality and social context (Silva et al, 2007;Perrone et al, 2009;Gavassa et al, 2012)], which relies on the activity of a well-known and accessible medullary medial nucleus (the PN) (Pouso et al, 2010;Quintana et al, 2011a;Quintana et al, 2011b), electric fish appear as a good model system to target specific brain areas of AVT actions. In a previous study, Perrone et al (Perrone et al, 2010) demonstrated that AVT induced a long-lasting and progressive increase of EOD rate in isolated B. gauderio, but had no effects in G. omarorum.…”
Section: Differential Avt Modulation Of Two Types Of Aggressionmentioning
confidence: 99%
“…The Pn drives the production of electric signals for electrocommunication and reproductive signaling and, in B. gauderio, its activity is modulated by social interactions and breeding conditions Quintana et al, 2010;Silva et al, 2007). For example, the nocturnal EOD rate of males is greater during the breeding season than during the non-breeding season and is further elevated when males are housed with females (Silva et al, 2007).…”
Section: Cell Proliferation and Environmental Complexitymentioning
confidence: 99%
“…The neuronal network (Figure 10) controlling the modulations of the EOD rate in Gymnotiformes is well characterized generally (Dye and Meyer, 1986; Metzner, 1999; Caputi et al, 2005) and consists of an unpaired medullary pacemaker nucleus (PN) containing two cell types: pacemaker (P) and relay cells (R). Apteronotid species also have a third PN cell type, but this has not been found in other gymnotiforms (Quintana et al, 2011). P-cells are smaller (50–100 μm) and have an intrinsically rhythmic activity (Bennett, 1968).…”
Section: Discussionmentioning
confidence: 96%
“…It is well known that P cells are electronically coupled via gap junctions, but relay cells are often also inter-connected with gap junctions, albeit with large and mostly unexplored species differences (Bennett et al, 1967). A more recent anatomical study (Quintana et al, 2011) of B. gauderio also suggested that there may be multiple populations of relay cells, allowing for network specializations that increase the diversity of outputs (rate changes). Relay cell differentiation might also be important for the coordination of electrocyte sub-populations in patterned activation patterns (e.g., Caputi, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation